Possibility of Improving Air Distribution and Heat Flow Conditions in Mechanical Grate Furnaces - Kozioł, Michał; Kozioł, Joachim (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One group of plants commonly used for solids combustion are grate furnaces. These furnaces come in numerous design solutions, dedicated to fuels with different properties and plants with different capacities. The use of grate furnaces presents the as-yet unresolved challenge of how to ensure the most favourable air distribution along the length of the grate.
Keywords: combustion; mechanical grate; furnace adjustment; furnace retrofit; low-emission combustion; combustion efficiency; air distribution; spalanie; ruszt mechaniczny; regulacja paleniska; modernizacja pieca; spalanie niskoemisyjne; efektywność spalania; dystrybucja powietrza